Prediction of the Total Peripheral Resistance of Healthy Men During Resistance Training (International Journal of Physiotherapy, 2024)
Background: Pulse pressure (PP) and mean blood pressure (MBP) are relatively convenient indicators of vascular function. This preliminary study investigated the effect of a single session of varying intensities of resistance training (RT) targeting the quadriceps femoris of healthy young men in the sitting position on the relationship between blood pressure and total peripheral resistance (TPR).Methods: Twenty-eight sedentary, healthy young men (mean age, 19.9 years; mean body mass, 63.4 kg; mean height, 171.2 cm; and mean body mass index, 21.5 kg/m2) were included. In a single session, the participants performed a total of 20 alternating knee extensions while sitting, with each excursion comprising a 5-s contraction and a 5-s rest period at 20%, 50%, and 80% load for a maximum of one repetition. During RT, we examined the correlations among MBP, PP, and TPR.Results: We observed a correlation between MBP and TPR at each exercise intensity (20%, r = 0.418, p = 0.027; 50%, r = 0.643, p = 0.0001; and 80%, r = 0.810; p = 0.0001).Conclusion: Changes in TPR during RT may be caused by changes in MBP.